Dynamic flow synthesis of porous organic cages. Issue 98 (14th October 2015) - Briggs, Michael E.; Slater, Anna G.; Lunt, Neil; Jiang, Shan; Little, Marc A.; Greenaway, Rebecca L.; Hasell, Tom; Battilocchio, Claudio; Ley, Steven V.; Cooper, Andrew I.
Abstract : Two imine-based porous organic cages were successfully synthesised in continuous flow. The same flow reactor was then used to scramble the constituents of these two cages in differing ratios to form cage mixtures. Abstract : The dynamic covalent synthesis of two imine-based porous organic cages was successfully transferred from batch to continuous flow. The same flow reactor was then used to scramble the constituents of these two cages in differing ratios to form cage mixtures. Preparative HPLC purification of one of these mixtures allowed rapid access to a desymmetrised cage molecule.